The Impact of Leadership Style and Organizational Culture on Employee Performance: The Mediating Role of Job Satisfaction - Fireni, Dian (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2025)
This study aims to examine the influence of leadership style and organizational culture on employee performance, with job satisfaction as an intervening variable, at the Regional Secretariat of Kerinci Regency. The research employs a quantitative causality design, with data collected through questionnaires distributed to employees. A probability sampling technique was applied, resulting in 95 distributed questionnaires, of which 70 were valid and processed. The data were analyzed using multiple linear regression with the assistance of the SmartPLS program.The findings reveal that leadership style has a significant effect on job satisfaction, and organizational culture also has a significant effect on job satisfaction. Additionally, both leadership style and organizational culture have a significant direct effect on employee performance. However, job satisfaction does not have a significant effect on employee performance. Furthermore, job satisfaction does not mediate the relationship between leadership style and employee performance, nor does it mediate the relationship between organizational culture and employee performance.